"Pieśń nad Pieśniami" w interpretacji Aponiusza - Stanisław Strękowski (Vox Patrum, 2012)
This article is the first attempt in Polish to present the main features of Aponius interpretation of the Song of Songs. For he was one of many authors who commented this book of the Old Testament, the content of which has always been a problem of interpretation. In ancient Christian times there were two exegetical currents: the literal and allegorical. Aponius falls within this second trend but brings individual and original exegesis off. In love of the bridegroom and the bride seems to see the symbol of love of the divine nature to human nature in the mystery of the Incarnation of the Son of God. By Aponius God himself comes through the Incarnation of the Word of the Father for his vineyard, which is the people of Israel, and through the precious seedlings originating from it and by the apostles, is revealed to the whole world, and through the seed of faith sown in individual peoples, creates a separate vineyards and offers the bride to the lavish use of the specific, unique fruits of welfare, to a shared joy in the vineyards.